Activation of PSGR with β-ionone suppresses prostate cancer progression by blocking androgen receptor nuclear translocation. (1st July 2019) - Xie, Hongjun; Liu, Tianjie; Chen, Jiaqi; Yang, Zhao; Xu, Shan; Fan, Yizeng; Zeng, Jin; Chen, Yule; Ma, Zhenkun; Gao, Yang; He, Dalin; Li, Lei
Abstract: The prostate-specific G protein-coupled receptor (PSGR) is a class A G protein-coupled receptor (GPCR) that is specifically expressed in prostate epithelial cells, and its expression has been linked to prostate cancer (PCa) progression. Here, we show that activation of PSGR with its ligand β-ionone, an end-ring analog of β-carotenoid, can suppress PCa cell growth both in vitro and in vivo model. Dissection of the mechanism underlying this relationship reveals that activation of PSGR by β-ionone suppresses AR nuclear translocation via phosphorylation of AR at residue Ser650 by p38 and JNK, which leads to the suppression of AR transactivation, further suppressing PCa cell growth. Overall, we link a cancer cell-specific GPCR with the nuclear AR and show that targeting PSGR can provide us a new target to combat PCa better. Highlights: Activation of PSGR by β-ionone suppresses AR-positive PCa cell growth. Activation of PSGR by β-ionone decreases AR transactivation without influencing AR expression. Activation of PSGR can suppress AR nuclear translocation via activation of the p38 and JNK signaling pathways. Activation of the p38 and JNK signaling pathways results in the phosphorylation of AR at residue Ser650.